Financial Structure and Macroeconomic Volatility: a Panel Data Analysis - Emiel F.S. van Bezooijen; Jacob A. Bikker (Utrecht University, Utrecht University School of Economics, Tjalling C. Koopmans Research Institute, 2017)
In 2015, the European Commission (EC) launched its action plan for the creation of a European Capital Markets Union. The EC aims to return the European economy to sustainable growth and to enhance its shock absorbing capacity by reducing the reliance on bank finance and stimulating financial deepening and cross-border integration of Europe's capital markets. Financial diversification and integrated European capital markets are expected to improve risk sharing among households, supporting economic stability. However, the economic literature reveals a lack of theoretical and empirical consensus on the superiority of either a bank-based or a market-based financial system in promoting growth or reducing macroeconomic volatility. This paper is the first to include bond markets in its financial structure indicators, besides stock markets and bank lending. Using panel data on 55 countries between 1975 and 2014 and three different measures of financial structure, we investigate the effect of the structure of the financial system on the volatility of output and investment growth as well as their cyclical components. We do not find evidence that market-based financial structures dampen volatility of output or overall investment. Increase of the stock market size relative to that of the banking sector has a significant positive effect on the business cycle volatility of investments.
Keywords: 330; financial developmen; financial system structure; macroeconomic volatility; market-based finance; bank-based finance; capital market integration; business cycle